Trypsin hydrolysis of whey protein concentrates: characterization using multivariate data analysis - Mota, M. V. T. (2006)
Hydrolysis of whey protein concentrates (WPCs) was performed using trypsin under different combinations of temperatures and pH values in a total of three experiments, namely experiment A at 37 ºC and pH 8, experiment B at 37 ºC and pH 9, and experiment C at 50 ºC and pH 8. Monitorization of the degradation of native whey proteins and the peptide formation throughout hydrolysis was performed by reverse phase HPLC/UV. Seven main peptides were separated according to their polarity and numbered from T1 to T7. In general a difference was observed between rate of hydrolysis of α-lactalbumin and β-lactoglobulin; in the former case hydrolysis was complete by 15 min in experiments B and C and by 120 min in experiment A, whereas in the later case the rate of hydrolysis was much slower. ANOVA analysis, performed to assess whether the average values obtained for the three experiments conducted to statistically different results for each variable (% of β-lactoglobulin degradation and % of peptides T1 to T7), showed significant differences between experiments A and C. However, between A and B and between B and C no significant differences were observed. Principal Component Analysis evidenced the time period at which similarities and/or differences between experiments were observed. Additionally, a mathematical equation for the degradation of β-lactoglobulin as a function of hydrolysis time was established and some peptides were correlated with their parental protein using linear regression analysis.